Pengaruh Pemberian Virgin Coconut Oil (VCO) Terhadap Luka Dekubitus Pada Pasien Tirah Baring Lama di RS. Stella Maris Makassar - Elmiana Bongga Linggi; Wirmando Wirmando; Mulya Kurnia; Nuni Tandi A. (FORIKES, 2021)
Decubitus wounds are still a serious problem both developed and in developing countries. Many patients suffering from decubitus injuries are primarily patients with chronic illnesses, very weak patients, and patients who are paralyzed over a long period time are even secondary problems that many hospitalized patients have experienced for a long time. The main cause of decubital wounds is due to the presence of pressure that can cause soft tissue ischemia, so it requires effective skincare to prevent the onset of decubital wounds. In addition to using methods with existing hospital standards for example giving left-leaning right-leaning positioning, it is also necessary to additional methods as a companion of methods that have run in hospitals such as the administration of non-pharmacological therapy namely Virgin Coconut Oil (VCO) whereby this oil has a good content to maintain skin health. The purpose of the study was to find out the influence of VCO on the prevention of decubitus wounds in long period bed patients in Stella Maris Makassar Hospital. This type of research was quasy experiment with pre-test and post-test nonequivalent control group design. Sampling techniques used non-probability sampling by the method of consecutive sampling. The sample size was 30 respondents, divided into two groups namely the case group (intervention) given VCO and the right-left slant position and the control group that only given left-leaning-right-leaning position intervention without the administration of VCO. Interventional grants were made for three consecutive days. The study used skin observation sheet instruments to identify the degree of decubitus wound and the test used namely the Mann–Whitney test, whereby obtained the p=0.011 (α